(untitled) (Indonesian Economic Justice Review, 2024)
This paper examines the persistent economic divide between urban and rural areas in Indonesia and the challenges associated with achieving inclusive growth. While Indonesia has experienced impressive economic growth in recent decades, urban areas have largely benefited more than rural regions, leading to significant disparities in income, infrastructure, and access to essential services. The paper investigates the underlying factors contributing to this gap, such as unequal access to education, healthcare, and technology, as well as differences in job opportunities and income generation. It also explores how rural communities are disproportionately affected by issues such as agricultural dependency, inadequate transportation infrastructure, and limited access to financial services. Drawing on both qualitative and quantitative data, the study analyzes government policies aimed at reducing rural-urban inequality, including rural development programs, subsidies for farmers, and infrastructure projects. However, the paper finds that these policies have often been insufficient in addressing the root causes of the economic divide. The study suggests that inclusive growth requires a holistic approach that not only focuses on infrastructure and access to resources but also addresses deeper issues such as labor market dynamics, education quality, and regional economic planning. The paper concludes with policy recommendations aimed at creating more equitable economic opportunities across the country.